2013
DOI: 10.1002/chem.201301035
|View full text |Cite
|
Sign up to set email alerts
|

Elementary Photoelectronic Processes at a Porphyrin Dye/Single‐Walled TiO2 Nanotube Hetero‐interface in Dye‐Sensitized Solar Cells: A First‐Principles Study

Abstract: A unique one-dimensional (1D) sandwich single-walled TiO2 nanotube (STNT) is proposed as a photoanode nanomaterial with perfect morphology and large specific surface area. We have thoroughly examined the elementary photoelectronic processes occurring at the porphyrin dye/STNT hetero-interface in dye-sensitized solar cells (DSSCs) by theoretical simulation. It is desirable to investigate the interfacial photoelectronic processes to elucidate the electron transfer and transport mechanism in 1D STNT-based DSSCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 101 publications
(119 reference statements)
1
2
0
Order By: Relevance
“…The bidentate adsorption mode is quite stable, (Supporting Information Figure S1), which is experimentally and theoretically confirmed for dye adsorption on the TiO 2 nanoparticles . The stable ZnPVB/TiO 2 structure is also confirmed by the binding strength with the adsorption energy of 1.20 eV, which is consistent with previous study . The optimized configuration of ZnPVB@TiO 2 was used for the following time‐dependent DFT (TD‐DFT) calculations.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The bidentate adsorption mode is quite stable, (Supporting Information Figure S1), which is experimentally and theoretically confirmed for dye adsorption on the TiO 2 nanoparticles . The stable ZnPVB/TiO 2 structure is also confirmed by the binding strength with the adsorption energy of 1.20 eV, which is consistent with previous study . The optimized configuration of ZnPVB@TiO 2 was used for the following time‐dependent DFT (TD‐DFT) calculations.…”
Section: Resultssupporting
confidence: 85%
“…To study the absorption spectrum, the excited states of deprotonated ZnPVB (ZnPVB‐H) on protonated TiO 2 (101) slab (TiO 2 +H) should be calculated. However, the excited states of ZnPVB‐H@TiO 2 +H cannot provide accurate electronic transitions because TiO 2 (101) slab items would get involved in these electronic transitions . Consequently, it is necessary to isolate the ZnPVB‐H from the sensitized system ZnPVB‐H@TiO 2 +H when TD‐DFT calculations are performed.…”
Section: Resultsmentioning
confidence: 99%
“…Because these 1D-nanowires have a more spatially accessible and organized structure, they facilitate the formation of uniform polysiloxane films to block more efficiently the interfacial recombination process at the interface, resulting in higher V OC and PCE. The use of 1D- and well-ordered TiO 2 -nanomaterials ,, as photoanodes, such as nanowires, , nanorods, nanotubes, , or nanobelt, has received great attention and appears as a promising alternative to suppress more efficiently these recombination processes at the TiO 2 /electrolyte interface. Following a different strategy, Chang et al reported the postadsorption of small molecules (a phenothiazine-based dye) on a porphyrin-sensitized TiO 2 anode surface, which is another approach to improve significantly the overall performance of a DSSC .…”
Section: Introductionmentioning
confidence: 99%